Maritime Security with Geospatial Integration For Indonesia’s Archipelagic Sea Lanes (ALKI) - Auriga Putri Faradilla; Rudiyanto; Widodo (Cita konsultindo, 2025)
Advances in digital technology have revolutionized the maritime sector through the use of Automatic Identification Systems (AIS), artificial intelligence (AI), remote sensing, and geospatial analytics, which are increasingly important in supporting Maritime Domain Awareness (MDA). Various studies show that AIS now functions as a strategic data source for predictive analytics, risk mapping, and even detecting anomalous vessel behavior, while big data and AI drive energy efficiency, logistics optimization, and intelligent navigation systems. Various methodological innovations can enable the integration of heterogeneous data to produce more accurate ship accident risk maps, while the combination of AIS with satellite imagery strengthens the detection of illegal activities such as IUU fishing in remote areas. Furthermore, the application of machine learning and deep learning algorithms has proven effective in detecting data manipulation and abnormal navigation patterns, thus strengthening early detection and rapid response systems. For Indonesia, which has strategic shipping lanes, the integration of these technologies is highly relevant to strengthen maritime surveillance, enhance maritime security, and maintain sovereignty amidst the region's geopolitical dynamics.